2017
DOI: 10.1063/1.4975394
|View full text |Cite
|
Sign up to set email alerts
|

Axisymmetric wall jet development in confined jet impingement

Abstract: The flow field surrounding an axisymmetric, confined, impinging jet was investigated with a focus on the early development of the triple-layered wall jet structure. Experiments were conducted using stereo particle image velocimetry at three different confinement gap heights (2, 4, and 8 jet diameters) across Reynolds numbers ranging from 1000 to 9000. The rotating flow structures within the confinement region and their interaction with the surrounding flow were dependent on the confinement gap height and Reyno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…These findings are attributed to the effect of jet impingement on the bluff endwall that influences the development of the resulting flow and are consistent with a previous study employing an unconfined single jet. 17 Hence, it can be concluded that the position of the ERZ exhibits a strong dependence on the aspect ratio L c /D c for low-swirl configurations (θ j = 5 • ), which is most significant for L c /D c < 2.…”
Section: A Mean Flow Fieldsmentioning
confidence: 90%
See 3 more Smart Citations
“…These findings are attributed to the effect of jet impingement on the bluff endwall that influences the development of the resulting flow and are consistent with a previous study employing an unconfined single jet. 17 Hence, it can be concluded that the position of the ERZ exhibits a strong dependence on the aspect ratio L c /D c for low-swirl configurations (θ j = 5 • ), which is most significant for L c /D c < 2.…”
Section: A Mean Flow Fieldsmentioning
confidence: 90%
“…Similarly, the PIV measurements of Long et al 10,11 found a strong dependence on jet angles (α j and θ j ) of the instantaneous and mean flow-fields generated with multiple symmetric jets. However, to the best of our knowledge, little or no information is available for the key geometrical parameters (e.g., L c and D c ) of the confined space for multiple jet configurations, although the aspect ratio of geometry has been found to have a significant influence on the flow-fields of free jet impingement [17][18][19] and cavity flow. [20][21][22] Importantly, the existing experimental data provide insufficient information to adequately understand the effect of the aspect ratio on the multiple confined jets in which both α j and θ j are variables.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Fig. 1, this implies that the flow field can be divided into three distinct regions: the free-jet, a stagnation region, and the wall-jet region (Guo et al, 2017 andYadav andAgrawal, 2018). Terzis (2016) correlated the flow dynamics and enhanced heat transfer by using both particle image velocimetry (PIV) and thermochromic liquid crystals (TLCs) to measure the flow field and local heat transfer rate, respectively.…”
Section: Introductionmentioning
confidence: 99%